Coffin‐Siris syndrome: Phenotypic evolution of a novel SMARCA4 mutation. Issue 7 (3rd April 2014) - Tzeng, Michael; du Souich, Christèle; Cheung, Helen Wing‐Hong; Boerkoel, Cornelius F.
<x xml:space="preserve">Abstract</x> Coffin‐Siris Syndrome (CSS) is an intellectual disability disorder caused by mutation of components of the SWI/SNF chromatin‐remodeling complex. We describe the evolution of the phenotypic features for a male patient with CSS from birth to age 7 years and 9 months and by review of reported CSS patients, we expand the phenotype to include neonatal and infantile hypertonia and upper airway obstruction. The propositus had a novel de novo heterozygous missense mutation in exon 17 of SMARCA4 (NM_001128849.1:c.2434C>T (NP_001122321.1:p.Leu812Phe)). This is the first reported mutation within motif Ia of the SMARCA4 SNF2 domain. In summary, SMARCA4‐associated CSS is a pleiotropic disorder in which the pathognomic clinical features evolve and for which the few reported individuals do not demonstrate a clear genotype–phenotype correlation. © 2014 Wiley Periodicals, Inc.